Reproductive biology and production of seeds and seedlings of Campomanesia pubescens (DC.) O. Berg. - Rodrigues,Sandra dos Santos (2017)
Abstract: Pollination is a fundamental process to produce food and maintain biodiversity in natural areas, since the production of seeds is related to its efficiency. Studies can determine the influence of reproductive systems on seed and seedlings quality and, consequently, on the structure of populations, helping the management, plant breeding and preservation of species. Campomanesia pubescens (DC.) O. Berg. (guabiroba) is a Brazilian shrub, pollinated by bees and occasionally by dipterans. This work aimed at evaluating the influence of pollination and reproductive system on seed production and germination and on the seedlings quality of C. pubescens. Phenology and floral biology were studied, and fruits from controlled pollinations were collected, in the Mogi Guaçu Biological Reserve, São Paulo State. The germination of seeds originated from self- and cross-pollination were analyzed, as well as the development of seedlings up to 180 days after germination. Seeds from self-pollination produced seedlings with lower development than the ones from cross-pollination, and they were more susceptible to mortality in laboratory and in greenhouse.